Process Optimization Of Biomass Combustion Of An Industrial Boiler In A Palm Oil Mill - Samsu, Muhammad Ariffin (Universiti Sains Malaysia, 2022)
Biomass is one of the major renewable energies used for production of power. Biomass generates power through combustion in a high-pressure environment. The energy from the process is transferred to produce high-pressure steam that will power up a steam turbine. Palm oil biomass especially empty fruit bunch (EFB), mesocarp fibre (MF), and palm kernel shell (PKS) has high potential to be utilized in local industrial boiler due to palm oil biomass is one of the most abundant biomasses available in Malaysia. However, the heating value from raw biomass is quite low compared to the conventional fuel which is diesel. This leads to insufficient power generation from biomass which requires addition of diesel to fulfil the electricity demand of the palm oil mill itself. Therefore, torrefaction is needed as pre-treatment to elevate the characteristics of the biomass especially EFB which exhibit high moisture content and low carbon content. Mixture of MF and PKS with 5,820 kg/h as feed in a boiler only produce 810 kWh of electricity compared to the electricity demand 990 kWh. However, by torrefaction of the biomass and addition of EFB, the electricity generated from the boiler can reach up to 940.917 kW which produce more power than the raw biomass. Additionally, increasing boiler temperature and air flow rate discretely increase the power generated. On the other hand, decreasing water flow rate increase the power generation. Finally, optimization to reach electricity demand by increasing the feed mass flow rate to 6,200 kg/h is achieved. 100% EFB alone able to produce 991.953 kWh while mixture of 50% EFB, 30% MF, and 20% PKS generates 1005.805 kWh of electricity.